The Influence of Organisational Climate on Organisational Commitment with Job Satisfaction as a Mediating Variable - I Made Fajar Hadiwinata; I Gede Riana (The Journal of Management, Digital Business, and Entrepreneurship, 2026)
This study aims to analyse the effect of organisational climate on job satisfaction and organisational commitment among employees of CV. Gandi Langit Adikara. The research population consisted of all company employees, and a saturated sampling technique was used, yielding 68 respondents. A quantitative approach with a causal research design was employed to examine the cause-and-effect relationships among the variables. Data analysis was conducted using descriptive and inferential analyses through Structural Equation Modelling–Partial Least Squares (SEM-PLS) to test the research hypotheses. The results indicate that organisational climate has a positive and significant effect on both organisational commitment and job satisfaction. In addition, job satisfaction has been shown to have a positive and significant effect on organisational commitment. Furthermore, the findings reveal that job satisfaction partially and complementarily mediates the effect of organisational climate on organisational commitment. These results suggest that a conducive organisational climate not only directly enhances employees’ organisational commitment but also indirectly strengthens it through increased job satisfaction. Theoretically, this study reinforces the organisational behaviour perspective, which emphasises the psychological work environment as a key determinant of employees’ work attitudes. A positive organisational climate serves as a social context that shapes employees’ perceptions, emotions, and attachment to the organisation, thereby sustainably enhancing job satisfaction and organisational commitment.